The Role of Spare Parts Availability and Maintenance Data for Sustainability Maintenance at PT. Djarum Kudus - Indrajaya, Hendy; Utomo, R. Hendra Priyo; Rachman, Tectony; Wardhani, Amie Kusuma (Research Horizon, 2024)
This research aims to develop a qualitative research model by identifying the implementation of maintenance at PT. Djarum and identifying the contribution of maintenance data and spare parts availability in selecting maintenance strategies. This research uses qualitative methods by conducting semi-structured interviews with representatives from PT. Djarum. The findings in this research are that maintenance data significantly influence the selection of machine maintenance strategies, and spare parts availability is not the primary factor in selecting machine maintenance strategies but contributes significantly. It is hoped that future research will be able to obtain more sources from other companies in the same sector as well as different sectors to compare the contributions of maintenance data and spare parts availability in their companies. Managerial implications for Machine Maintenance Service Companies in Improving Company Service Performance. This study explains the contribution of Maintenance Data and Spare Parts Availability to the performance of machine maintenance strategies in a company. This research model is used to determine the contribution of maintenance data and spare parts availability in improving the selection of machine maintenance strategies in the company.